On the Stojadinović–Pavelić Agreement from 1954 (Facts and Assumptions) - Simić, Bojan V. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The key figure among Serbian immigrants in Argentina was Milan Stojadinović, the former Prime Minister of the Kingdom of Yugoslavia, despite he did not take any official position in such emigrant organizations. Instead, he was rather a kind of consultant to both the organization Velika Srbija and their leading newspapers Srpska zastava. On the other hand, he used his influence acquired within the Serbian community in Argentina to negotiate with the representatives of socialist Yugoslavia during 1952 and 1953. The question of the Ustasha movement and his leader Pavelić, who has been in Argentina since 1948, was one of the main issues that troubled Yugoslavia– Argentine relations in the first decade after the Second World War. Argentina tolerated their activities which made Yugoslavia protest. They had their meetings and even formed a government in exile whose activities were aimed directly against the integrity of Yugoslavia. In 1951, the Yugoslav government issued an extradition warrant, but with no success. The response never arrived. Stojadinović and Pavelić met in Argentina during the 1950s, visited each other, but the product of this relationship remained uncertain and unclear. What is obvious is the fact that Stojadinović and Pavelić in 1954 reached some kind of agreement. That agreement provided for the break up of Yugoslavia and the formation of independent states of Serbia and Croatia. However, it was most likely left unsigned. The possible motivation for the agreement may lie in a series of factors, from foreign pressure against socialist Yugoslavia to personal agendas, a desire to return to power. Political changes in Argentina after the fall of Juan Peron in 1955 forced Stojadinović to distance himself from the Serbian emigrant community while Pavelić was forced to deny any connection with the Peron’s regime. The agreement between the two left unresolved and became a kind of controversy for future research.